OlympiAD extended follow-up for overall survival and safety: Olaparib versus chemotherapy treatment of physician's choice in patients with a germline BRCA mutation and HER2-negative metastatic breast cancer. (May 2023) - Robson, Mark E.; Im, Seock-Ah; Senkus, Elzbieta; Xu, Binghe; Domchek, Susan M.; Masuda, Norikazu; Delaloge, Suzette; Tung, Nadine; Armstrong, Anne; Dymond, Mike; Fielding, Anitra; Allen, Allison; et al.
Abstract: Background: In the Phase III OlympiAD study, olaparib significantly prolonged progression-free survival versus chemotherapy treatment of physician's choice (TPC) in patients with germline BRCA-mutated (gBRCAm), human epidermal growth factor receptor 2-negative metastatic breast cancer (mBC). In the final pre-specified analysis (64% maturity), median overall survival (OS) was 19.3 months for olaparib and 17.1 months for TPC ( P = 0.513). Post-hoc extended follow-up, 25.7 months longer than previously reported for OS, is reported. Patients and methods: Patients with gBRCAm, human epidermal growth factor receptor 2-negative mBC, who had received ≤2 lines of chemotherapy for metastatic disease, were randomised 2:1 to olaparib (300 mg bid) or TPC. During extended follow-up, OS was analysed every 6 months using the stratified log-rank test (overall population) and Cox proportional hazards model (pre-specified subgroups). Results: In the overall population (302 patients; 76.8% maturity), median OS was 19.3 months for olaparib and 17.1 months for TPC (hazard ratio 0.89, 95% confidence interval 0.67–1.18); median follow-up was 18.9 and 15.5 months, respectively. Three-year survival was 27.9% for olaparib versus 21.2% for TPC. With olaparib, 8.8% of patients received study treatment for ≥3 years versus none with TPC. In first-line mBC, median OS was longer for olaparib than TPC (22.6 versus 14.7 months; hazard ratio 0.55, 95% confidence interval 0.33–0.95) and 3-year survival was 40.8% for olaparib versus 12.8% for TPC. No new serious adverse events related to olaparib were observed. Conclusions: OS was consistent with previous analyses from OlympiAD. These findings support the possibility of meaningful long-term survival benefit with olaparib, particularly in first-line mBC. Highlights: Median overall survival (OS) was 19.3 and 17.1 months for olaparib versus chemotherapy treatment of physician's choice (TPC), respectively. Overall, 8.8% of patients received at least 3 years of study treatment in the olaparib arm versus no patients in the TPC arm. In first-line, median OS was numerically longer for olaparib versus TPC (22.6 versus 14.7 months, respectively). In first-line, the 3-year OS rate was 40.8% for olaparib versus 12.8% for TPC. These data confirm previous findings and suggest a possible OS benefit for olaparib in the first-line metastatic breast cancer setting.